2016
DOI: 10.1177/2211068215569347
|View full text |Cite
|
Sign up to set email alerts
|

Improving Laboratory Efficiency by Automation of Preanalytic Processing of ThinPrep Specimens for Real-Time PCR High-Risk HPV Testing

Abstract: Cervical specimens collected in liquid-based cytology (LBC) media are the most common sample type used for high-risk human papillomavirus (HPV) testing. Since preanalytic steps such as vortexing and decapping vials, liquid transfer to a sample input tube with matching unique identifier, and recapping the original vials are required for processing LBC samples prior to running the Abbott RealTime High Risk HPV assay (Abbott, Wiesbaden, Germany), a full manual execution can be complicated, especially in high-thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…The automation of pre‐processing ThinPrep samples using the Tecan Freedom EVO 150 instrument has previously been described in a study in Italy, demonstrating reproducibility and improved reliability of test results following automated pre‐processing of cervical specimens collected in original ThinPrep LBC vials after cytological analysis. Our study represents the first report on the performance of the automated Tecan EVO system for processing SurePath LBC prior to testing on the Abbott m 2000 System, comparing its performance to manual aliquoting for both triage and HPV primary samples, using sample material that was not depleted from cells or liquid by a cytology processor.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…The automation of pre‐processing ThinPrep samples using the Tecan Freedom EVO 150 instrument has previously been described in a study in Italy, demonstrating reproducibility and improved reliability of test results following automated pre‐processing of cervical specimens collected in original ThinPrep LBC vials after cytological analysis. Our study represents the first report on the performance of the automated Tecan EVO system for processing SurePath LBC prior to testing on the Abbott m 2000 System, comparing its performance to manual aliquoting for both triage and HPV primary samples, using sample material that was not depleted from cells or liquid by a cytology processor.…”
Section: Discussionsupporting
confidence: 71%
“…The Freedom EVO 150 instrument (Tecan EVO) is used by laboratories to automate a diverse range of applications and has previously been described in a study for pre‐processing ThinPrep LBC samples conducted in Italy . On a limited number of specimens, Barbieri et al demonstrated that automated pre‐processing leads to higher reproducibility of signal measured with RT hrHPV.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…LBC also allows for the molecular testing of HPV from the same vial, as long as approximately 2 mL of sample is sent for molecular biology first (to avoid contamination), and then routine LBC preparation is carried out. [ 13 , 14 ] For laboratories accredited by CAP, the cytopathology checklist provides benchmarking data for the acceptable reporting-percentile rate (RPR) for each category and ASC/SIL ratio for each preparation type. [ 9 ] Our data, percentages and ASC/SIL ratios, as shown in [ Table 1 ], were within the 5–95 th RPR; due to copyright, we cannot share the CAP’s RPR in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The steps involved in LBC are easily automated, making the process more efficient and less dependent on manual skills. This automation extends to screening, with several platforms allowing automated primary screening of LBC samples 22 . This dramatically increases the throughput of samples, essential in large-scale screening programs.…”
Section: Standardization and Automationmentioning
confidence: 99%